In Silico Study of a-Amylase and a-Glucosidase Inhibitory Compounds in Aloe vera as Antidiabetic Agent - M. Nizam Zulfi Zakaria; Ahmad Fariduddin Aththar; Syeftyan Muhammad Ali Hamami; Michelle Fai; Sri Rahayu (Biotropika: Journal of Tropical Biology, 2023)
Type 2 diabetes mellitus (T2DM) is a chronic disease that poses a significant global health issue. The most commonly given drug to treat diabetes is acarbose, which works as an inhibitor of polysaccharide-degrading enzymes, such as alpha amylase dan alpha glucosidase so that the blood glucose level in T2DM patients could be reduced. This study aims to analyse five bioactive aloe vera compounds as inhibitors of alpha amylase and alpha glucosidase enzymes. This research was conducted through in silico studies based on molecular docking using PyRx 0.8 and Biovia Discovery Studio software, cytotoxicity testing through pkCSM and feasibility of medicinal materials through ADMET analysis. The results showed that hesperidin has a binding affinity of -9.1 kcal/mol against the alpha amylase enzyme. Meanwhile, acarbose, as a control, showed a binding affinity of -8.5 kcal/mol. In addition, osajin, pomiferin, cosmosiin, and hesperidin had a binding affinity of -7.8, -8.1, -7.7, and -8.8 kcal/mol, respectively. These values were also higher than acarbose (-7.3 kcal/mol). Three compounds, namely osajin, pomiferin, and aloesin, met the drug-likeness criteria and had absorption rates in the digestive tract between 31.48-96.59%. The toxicity analysis using the AMES test revealed that all compounds, except aloesin, did not exhibit properties that could potentially cause hepatotoxicity or promote mutagenesis. These results indicate that the bioactive compounds in Aloe vera have the potential to be used as antidiabetic agents through the inhibition of polysaccharide-degrading enzymes. Further research is needed to analyze the antidiabetic properties of the compounds in Aloe vera through in vivo studies with more optimal drug delivery innovations.